Consumer Protection Agency’s crisis management for children’s kidney failure cases in Indonesia - Libraveda, Lesca Terlly; Natalia, El Chris (Jurnal Kajian Komunikasi, 2024)
Background: The Badan Perlindungan Konsumen Nasional Republik Indonesia (BPKN RI) is a government institution dedicated to protect consumer rights nationwide. In August 2022, instances of kidney disorders affecting children emerged in various regions of Indonesia, necessitating BPKN’s involvement in addressing these cases. Purpose: This study examines how crisis communication factored into BPKN RI’s crisis management strategy during the 2022 outbreak of atypical progressive acute kidney injury (APAKI) in children. Methods: The theoretical framework guiding this research encompasses organizational theory, corporate communication theory, crisis communication theory, and crisis management theory. Employing a descriptive qualitative approach, data collection involves interviews, internet observations, and document analysis. Interviews were conducted with key figures, including the secretary of BPKN RI, the Public Relations and Education Division of BPKN RI, and the Investigation Team for APAKI cases in children. Results: The research findings reveal that BPKN RI’s crisis management process involves identifying the crisis, analyzing its implications, isolating the crisis, formulating a strategy, and implementing a crisis control program, with crisis communication as the fundamental element of the crisis management strategy. Conclusion: BPKN RI’s crisis management strategy prioritizes public welfare, ensuring easy public access, and maintaining transparency and honesty. Implications: BPKN RI disseminates regular and periodic information to the public, designates the Chairman of BPKN RI as the spokesperson, monitors community sentiments and media coverage, and establishes a public information center.